2019
DOI: 10.1155/2019/2352941
|View full text |Cite
|
Sign up to set email alerts
|

A Quality of Experience Management Framework for Mobile Users

Abstract: Voice transmission is no longer the main usage of mobile phones. Data transmissions, in particular Internet access, are very common actions that we might perform with these devices. However, the spectacular growth of the mobile data demand in 5G mobile communication systems leads to a reduction of the resources assigned to each device. Therefore, to avoid situations in which the Quality of Experience (QoE) would be negatively affected, an automated system for degradation detection of video streaming is propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Similarly, Wassermann et al [72] suggested that YouTube mobile QoE can be realized via machine learning models (e.g., random forests) with high accuracy using only network-related features. In turn, Algar et al [73] proposed an automated realtime video QoE management framework for mobile users depending on the network traffic policies and user actions. Besides above wroks, Mrvelj and Matulin [74] studied user's QoE in real life environments by examining the impact of packet loss related issues in User Datagram Protocol (UDP) when 1-h multimedia content (e.g., a TV program) were streamed.…”
Section: A Influencing Factorsmentioning
confidence: 99%
“…Similarly, Wassermann et al [72] suggested that YouTube mobile QoE can be realized via machine learning models (e.g., random forests) with high accuracy using only network-related features. In turn, Algar et al [73] proposed an automated realtime video QoE management framework for mobile users depending on the network traffic policies and user actions. Besides above wroks, Mrvelj and Matulin [74] studied user's QoE in real life environments by examining the impact of packet loss related issues in User Datagram Protocol (UDP) when 1-h multimedia content (e.g., a TV program) were streamed.…”
Section: A Influencing Factorsmentioning
confidence: 99%
“…• Slice provisioning (instantiation) may utilize well-defined usage types through clustering, in order to select appropriate templates for the slices based on predicted requirements [3]. • Quality of Experience (QoE) estimation tries to map explicitly measurable Key Performance Indicators (KPIs), such as network delay, jitter or throughput to user satisfaction levels [4]. Here, clustering may be utilized to establish user archetypes.…”
Section: Introductionmentioning
confidence: 99%